VENOTONIC DRUGS APPLICATION BASEMENT IN PATIENTS WITH FETOPLACENTAL INSUFFICIENSY - Grishchenko, O.V.; Lakhno, I.V.; Ovcharenko, A.T.; Dudko, V.L. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Venous vessels incompetence during pregnancy is assotiated with decreased venous drainage from intervillous space, myometrial sinuses and parametrial veins. These changes are connected with fetoplacental insufficiensy which is due to the systemic inflammafory response. The inflammation induces disorders of connective tissue and cell membranes of fetoplacental system. We have investigated the theraputical effectiveness of bilberry vita complex and venotonic drug phlebodia in pregnant womenwithfetoplacental insufficiensy. We have observed 64 patients with fetoplacentalinsufficiensy at term of pregnancy 34-36 weeks and 37 of them were taken bilberry vita complex 1 capsule twice per day and phlebodia 1 pill once daily. Inall inverstigated patients were determined the activity of lipid peroxidation with biochemiluministry of blood serum method andintrauterine fetus well-being assessment. We have proved that fetoplacental insufficiensy was accompanied with oxidative stress that have promoted to the destruction of connective tissual structures in venous vessels. It was charactetized with low uteroplacental hemodynamics and chronic fetal distress. The application of bilberry vita complex and phlebodia have improved hemocirculation in the vessels of small pelvis, placenta and fetus and fetal well-being in higher degree than traditional therapy.